PENGARUH KINERJA LINGKUNGAN TERHADAP KINERJA KEUANGAN: STUDI PADA PERUSAHAAN YANG TERDAFTAR DI KEMENTERIAN LINGKUNGAN HIDUP DAN LISTING DI BEI (PERIODE 2008-2014) - Akhsan, Abdul Aziz Nurul; Muharam, Harjum (Diponegoro Journal of Management, 2016)
The aim of this study is to examine the impact of corporate environmental performance toward corporate financial performance. Corporate environmental performance is measured by the score of PROPER published by the Ministry of Environment of the Republic of Indonesia, and corporate financial performance is measured using ROA and Tobin’s q. The population in this study is all go public companies listed on Indonesia Stock Exchange (BEI) and listed on PROPER appraisal in 2008 – 2014. The sampling method used in this study is purposive sampling. By doing sampling and processing data, the final amounts of the sample are 18 firms. This study uses multivariate regression analysis technique to examine the hypotheses. The result shows that improving corporate Environmental Performance significantly influence corporate Financial Performance.